2004
DOI: 10.1590/s1677-55382004000600008
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral endometriosis and coexistent urethral leiomyoma in a postmenopausal woman

Abstract: We report the case of a postmenopausal woman with a synchronous obstructing intrinsic endometrioma of the left ureter and a coexistent periurethral leiomyoma. Endometriosis in postmenopausal women is a rare clinical entity usually associated with exogenous estrogen use. Urethral leiomyomas are also rare, with only 40 cases reported in the literature. Ovarian hormones are believed to influence the growth of leiomyomas. We report the genitourinary presentation of 2 separate disease entities with known hormonal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 3 publications
(6 reference statements)
0
13
0
1
Order By: Relevance
“…Rare cases of ureteral endometriosis in postmenopausal women are reported, and in most of these women, there is a history of prolonged estrogen therapy or excessive production of estrogen by the adrenals or pituitary gland [9][10][11][12]. It has been proposed that delayed presentation of ureteral endometriosis associated with extensive renal scarring, with onset well IT IT IT IT IT IT IT IT IT IT before menopause, accounts for most cases of endometriosis in postmenopausal women [3].…”
Section: Discussionmentioning
confidence: 99%
“…Rare cases of ureteral endometriosis in postmenopausal women are reported, and in most of these women, there is a history of prolonged estrogen therapy or excessive production of estrogen by the adrenals or pituitary gland [9][10][11][12]. It has been proposed that delayed presentation of ureteral endometriosis associated with extensive renal scarring, with onset well IT IT IT IT IT IT IT IT IT IT before menopause, accounts for most cases of endometriosis in postmenopausal women [3].…”
Section: Discussionmentioning
confidence: 99%
“…The cases of leiomyoma developing before puberty are rare; it mainly occurs in the 30s and 40s when female hormones are released most actively, and the size of leiomyoma may be decreased after menopause. Hence, it may be influenced by female hormone [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to numerous studies on the association with female hormone that showed evidence contradictory to each other [16,26,29,30]. Therefore, leiomyoma may be developed by other causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of pelvic endometriosis is high, affecting approximately 6-10% of women of reproductive age 1 ; intestinal disease incidence varies from 3 to 34% 2 . Although endometriosis has been associated with the occurrence of menstrual cycles, it can affect between 2 and 5% of postmenopausal patients [3][4][5] , and generally occurs as a side-effect of hormone use [6][7][8][9] . In these cases, differential diagnosis with malignancies is critical.…”
Section: Introductionmentioning
confidence: 99%